Beyond dams: assessing integrated water storage in the Shashe Catchment, Limpopo River Basin - Ebrahim, Girma Yimer; Lautze, Jonathan F.; McCartney, Matthew P.; Matheswaran, Karthikeyan; Nyikadzino, B.; Tafesse, N. T. (Elsevier, 2024)
Study region: The Shashe catchment, Limpopo River Basin, Botswana, and Zimbabwe.